SA@CDs / g-C3N4 composite material, its preparation method and use in aflatoxin removal

The SA@CDs/g-C3N4 composite addresses the inefficiencies of existing aflatoxin removal methods by providing a safe and effective solution that maintains food quality and facilitates easy recycling.

JP7605541B1Active Publication Date: 2024-12-24QINGDAO AGRI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024078028
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-06
Filing Date
2024-05-13
Publication Date
2024-12-24
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

Current aflatoxin removal methods, such as physical and chemical treatments, result in nutritional loss, structural damage, and the introduction of harmful substances, making them unsuitable for modern agricultural products.

Method used

A composite material, SA@CDs/g-C3N4, is prepared by ultrasonic dispersion, sodium alginate mixing, freeze-drying, and high-temperature baking, which effectively removes aflatoxin from food without significant nutritional loss.

Benefits of technology

The composite material safely and efficiently removes aflatoxin, maintaining food quality and facilitating easy recycling, while avoiding the introduction of harmful residues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605541000001_ABST
    Figure 0007605541000001_ABST
Patent Text Reader

Abstract

Provided is a SA@CDs / g-C3N4 composite material, its preparation method and its use, which can effectively remove aflatoxin residues in food, has a mild effect, is environmentally friendly, safe, easy to recycle, and can avoid the impact of material residues on food quality. [Solution] The CDs / g-C3N4 composite is added to water, ultrasonicated to disperse it uniformly, then sodium alginate is added, vigorously stirred and mixed thoroughly to form a pre-gel solution, the thoroughly mixed pre-gel solution is transferred to a mold, and then freeze-dried to obtain a solid sponge, the solid sponge is immersed in CaCl2 solution to gel, and then washed with deionized water and freeze-dried to obtain the SA@CDs / g-C3N4 composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of organic materials, specifically to SA@CDs / g-C3N4 composite material, its preparation method and use in aflatoxin removal. [Background technology]

[0002] Foods such as grains, edible oils, and meat are susceptible to environmental pollution during cultivation, storage, and breeding, which can cause food safety problems. In addition, disease-causing microorganisms may grow in these foods and form mycotoxins, of which a representative mycotoxin is aflatoxin (AFT), which can cause significant economic losses and health damage. How to neutralize this is a major challenge for the food industry. Currently, there are physical and chemical methods for removing aflatoxins. Chemical methods generally use strong oxidizing agents (ozone, hydrogen peroxide, etc.), and treating agricultural products and foods with these strong oxidizing agents can achieve good removal of aflatoxins, but they destroy the structure of the nutritional and flavor substances in agricultural products, affecting the flavor and nutrition of the products and limiting scale-up. Physical methods generally use high-temperature treatment, and some of the flavors and nutrients that have low boiling points and are unstable are destroyed after high-temperature treatment. Therefore, these methods have the disadvantages of unstable effects, large loss of nutrients, and the introduction of new harmful components, making it difficult to meet the demands of the development of the modern agricultural product industry. Therefore, it is of great significance to explore more environmentally friendly, effective and safe methods for removing aflatoxins from food. Summary of the Invention

[0003] The present invention provides a method for preparing SA@CDs / g-C3N4 composite material, the steps of which are as follows: The CDs / g-C3N4 composite is added to water and ultrasonicated to disperse it uniformly, then sodium alginate is added, vigorously stirred and mixed thoroughly to form a pregel solution, the well-mixed pregel solution is transferred to a mold and then freeze-dried to obtain a solid sponge, the solid sponge is immersed in CaCl2 solution to gel, and then washed with deionized water and freeze-dried to obtain the SA@CDs / g-C3N4 composite. In the above method for preparing SA@CDs / g-C3N4 composite material, the mass volume ratio of CDs / g-C3N4 composite to water is selected from 1:300 to 1:800, and preferably is 1:500, g / mL. In the above-mentioned method for preparing SA@CDs / g-C3N4 composite material, the mass ratio of CDs / g-C3N4 composite to sodium alginate is selected from 1:4 to 1:10, and preferably is 1:7.5. In the above method for preparing the SA@CDs / g-C3N4 composite material, the concentration of CaCl2 solution is selected from 1-8 wt%, and preferably is 3 wt%. The present invention provides a method for preparing said CDs / g-C3N4 composite, the steps of which are as follows: Melamine and trithiocyanuric acid are added to water and stirred uniformly, then CDs solution is added and stirred uniformly, the mixed solution is filtered, washed and dried, and transferred to a muffle furnace and calcined at high temperature to obtain the CDs / g-C3N4 composite. In the above preparation method of CDs / g-C3N4 composite, the molar ratio of melamine to trithiocyanuric acid is selected from 1:0.5 to 1:1.5, preferably 1:1. In the above preparation method of CDs / g-C3N4 composite, the molar volume ratio of melamine to water is selected from 1:4000 to 1:8000, preferably 1:6000, mol / mL. In the above preparation method of CDs / g-C3N4 composite, the volume ratio of CDs solution to water is selected from 1-7:60, preferably 3:60. In the preparation method of the above CDs / g-C3N4 composite, the high-temperature calcination conditions are as follows: increase the temperature to 550-650°C at a rate of 2-6°C / min and calcinate at this temperature for 3-6 hours, preferably increase the temperature to 600°C at a rate of 3°C / min and calcinate at this temperature for 4 hours. The present invention provides a method for preparing the above-mentioned CDs solution, the steps of which are as follows: Orange juice is placed in a polytetrafluoroethylene-lined reactor and heated to high temperature. After natural cooling, the reaction product is centrifuged and filtered to form a transparent brown-yellow carbon quantum dot solution, i.e., CDs solution. In the above-mentioned method for preparing the CDs solution, the high-temperature heating conditions include heating at 180 to 210° C. for 8 to 12 hours, and preferably heating at 200° C. for 10 hours. The present invention provides the SA@CDs / g-C3N4 composite material prepared by the above method. The present invention provides a use of the above SA@CDs / g-C3N4 composite material in removing aflatoxin from food, wherein the aflatoxin is selected from aflatoxin B1. Effect of the Invention

[0004] The present invention has the following beneficial effects: The SA@CDs / g-C3N4 composite material prepared according to the present invention can effectively remove aflatoxin residues in food, has a mild action, is environmentally friendly, safe, and easy to recycle, and can avoid the impact of material residues on food quality. [Brief description of the drawings]

[0005] [Figure 1] 1 shows the XRD patterns and FTIR spectra of carbon quantum dots solution, where a is the XRD pattern and b is the FTIR spectrum. [Diagram 2]SEM, TEM, HRTEM and TEM-EDX elemental mapping diagrams of STCN and CSTCN-3, where a is the SEM diagram of STCN, b and c are TEM images under different multiples of STCN, d is the SEM diagram of CSTCN-3, e–g are TEM images under different multiples of CSTCN-3, h is the HRTEM diagram (inset is SAED image), and i–l are the corresponding TEM-EDX elemental patterns of CSTCN-3. [Diagram 3] 1 shows the XRD pattern (a), FT-IR spectrum (b), UV-vis absorption spectrum (c), PL spectrum (d), EIS diagram (e) and transient photocurrent response (f) of the product obtained in step (2) of Example 1, where in c, the curves are CSTCN-7, CSTCN-5, CSTCN-3, CSTCN-1, STCN from top to bottom, in d, the curves are STCN, CSTCN-3, CSTCN-1, CSTCN-5, CSTCN-7 from top to bottom, in e, the curves are CSTCN-3, CSTCN-7, CSTCN-5, STCN, CSTCN-1 from left to right, and in f, the curves are CSTCN-3, CSTCN-5, CSTCN-7, CSTCN-1, STCN from top to bottom. [Figure 4] High-resolution XPS spectra of STCN and CSTCN-3. [Diagram 5] Flowchart of the preparation of SA@CSTCN sponge (a), external view of SA sponge and SA@CSTCN sponge (b), surface view of SA@CSTCN sponge (c), and cross section of SA@CSTCN sponge (d). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Other materials used in the present invention are available through commercial sources unless otherwise specified.Other terms used in the present invention generally have the meanings commonly understood by those skilled in the art unless otherwise specified.The present invention will be described in more detail below with reference to data in connection with specific embodiments.The following examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention in any way.

[0007] Example 1 The SA@CDs / g-C3N4 composite was prepared, and the steps are as follows: (1) Preparation of carbon quantum dot solution 30 mL of orange juice from fresh oranges is added to a 100 mL reactor lined with polytetrafluoroethylene and heated at 200 °C for 10 h. After natural cooling, the reaction product is centrifuged and filtered through a 0.22 μm polyethersulfone filter to form a transparent brown-yellow carbon quantum dots (CDs) solution. The XRD pattern and FTIR spectrum of the carbon quantum dot solution are shown in Figure 1. As can be seen from Figure 1, the prepared carbon quantum dots have an amorphous structure and have functional groups such as carbonyl groups and hydroxyl groups on the surface. (2) Preparation of CDs / g-C3N4 composite 1.26g melamine (0.01mol) and 3.16g trithiocyanuric acid (0.01mol) were added to 60mL deionized water and stirred for 1h to obtain a homogeneous mixed solution, and a certain volume (1mL, 3mL, 5mL and 7mL, respectively) of CDs solution was added to the above mixed solution and stirred for 12h. The mixed solution was filtered, washed and dried, and transferred to a muffle furnace, heated to 600°C at a rate of 3°C / min, and calcined at this temperature for 4h to obtain CDs / g-C3N4 composite, abbreviated as CSTCN-x photocatalyst, where x=1, 3, 5 and 7, i.e., the products obtained under the preparation conditions of 1mL, 3mL, 5mL and 7mL of CDs solution, respectively. For comparison, in the present invention, the product prepared under the same conditions without adding CDs solution is abbreviated as STCN.

[0008] The physical characteristics of the prepared CSTCN-3 and STCN are identified as shown in Fig. 2, where a is the SEM image of STCN, b and c are the TEM images of STCN under different multiples, d is the SEM image of CSTCN-3, e–g are the TEM images of CSTCN-3 under different multiples, h is the HRTEM image (the inset is the SAED image), and i–l are the corresponding TEM-EDX elemental patterns of CSTCN-3.

[0009] The micromorphology of STCN and CSTCN-3 is observed by SEM images. As can be seen from Fig. 2a, STCN has a nanorod structure, and as can be seen from Fig. 2d, after doping with CDs, CSTCN-3 maintains the nanorod structure, but a large number of holes are generated on the surface. As can be clearly seen from the TEM images in Fig. 2b and Fig. 2e, both STCN and CSTCN-3 are hollow structures, and as can be seen from Fig. 2c and Fig. 2f, CSTCN-3 has thin walls, which can be attributed to the large amount of gas released during the calcination process. As can be seen from the enlarged TEM image of CSTCN-3 shown in Fig. 2g, CDs were successfully doped into STCN. As can be seen from Fig. 2h, lattice streaks belonging to the carbon (001) crystal plane appear in the HRTEM, which further indicates that CDs are tightly bonded to STCN. Moreover, as can be seen from the related TEM-EDX elemental patterns of CSTCN-3 shown in Fig. 2i-l, C, N, O and S are uniformly distributed in the sample. The above results confirm that the citrus-derived CDs were successfully immobilized onto g-C3N4 nanotubes.

[0010] Figure 3 shows the XRD pattern (a), FT-IR spectrum (b), UV-vis absorption spectrum (c), PL spectrum (d), EIS diagram (e) and transient photocurrent response (f) of the product obtained in step (2) above. Regarding the crystal structure of the prepared g-C3N4 materials, as can be seen from the XRD spectra, all samples exhibited similar two characteristic diffraction peaks, as shown in Fig. 3a, the broad peak at 13.1° corresponds to the in-plane repeat motif of tris-s-triazine rings, and the sharp peak at 27.3° is attributed to the facet stacking of conjugated aromatic units. Similar to the XRD images, the FT-IR spectra of all samples showed almost the same characteristic peaks, with a peak at 816 cm, as shown in Fig. 3b. -1 The sharp peak at 1100–1750 cm is due to the formation of heptadine. -1 The multiple peaks at 3000~3500cm are due to the stretching vibration of the CN heterocycle. -1 The broad peaks in the range are attributed to the adsorbed water and NH stretching vibration.The CSTCN-x curves modified with CDs did not show significant changes compared to STCN, indicating that the crystal and molecular structure of STCN in the composites were not affected by CDs.

[0011] Enhancement of light absorption is one of the most effective ways to improve the catalytic performance of photocatalysts. As shown in Figure 3c, the quantum effect of CDs significantly enhanced the light absorption ability of CSTCN-x composites. And the absorption was further promoted with increasing quantum dot concentration. The color of the samples gradually changed from yellow to brown. Photoluminescence and time-resolved photoluminescence were used to measure the separation and transfer efficiency of photogenerated carriers. As shown in Figure 3d, after the introduction of CDs, CSTCN-x composites showed lower PL intensity than STCN. This result indicates that the introduction of CDs can effectively promote carrier separation. To further evaluate the effective photogenerated carrier separation and transfer efficiency in CSTCN-x, electrochemical characterization was performed. Figure 3e shows the electrochemical impedance spectrum (EIS) of the prepared catalyst. Compared with STCN, CSTCN-3 exhibits a shorter arc radius, which suggests a smaller charge transfer resistance and a more effective charge separation efficiency. Furthermore, as shown in Figure 3f, CSTCN-3 exhibits the highest photocurrent response intensity in repeated cycles of "switching" illumination, indicating a faster carrier transport rate in visible light. As can be seen from this, CSTCN-3 has the best photocatalytic performance. However, with the increase in CDs doping concentration, the photocurrent response intensity decreases, which is probably due to the introduction of new complex sites due to the increase in CDs.

[0012] Figure 4 shows the high-resolution XPS spectra of STCN and CSTCN-3. The XPS spectra were used to analyze the surface components and elemental composition of the prepared samples. The high-resolution C1s spectrum in Figure 4a can be deconvoluted into two peaks with binding energies of 284.7 and 287.9 ​​eV, which are attributed to CC / C=C and NC=N, respectively. As shown in Figure 4b, the N1s spectrum can be fitted into three peaks located at 398.4, 399.9 and 401.1 eV. These peaks correspond to CN=C, N-(C)3 and N-Hx, respectively. Figure 4c shows three peaks obtained in the high-resolution O1s spectrum, which are attributed to C=O at 531.5 eV, CO at 532.2 eV and OH / adsorbed water at 533.3 eV, respectively. It should be noted that compared to STCN, the content of C=O and CO on the surface of CSTCN-3 is significantly increased, which can be attributed to the presence of a large number of oxygen-containing functional groups on the CD surface. The high-resolution S2p spectrum showed a weak S element signal. The peak at 163.4 eV was identified as S-N bond, and the peak at 162.8 eV was identified as the formation of sulfur oxides. In addition, the O1s peaks in CSTCN-3 were all shifted to lower binding energy, which suggested the existence of electron flow in the CDs in the composite. Since CSTCN-3 has the best photocatalytic performance, in the present invention, CSTCN-3 was directly used to prepare the SA@CSTCN composite as shown in the following step (3).

[0013] (3) Preparation of SA@CDs / g-C3N4 composite 0.1 g of CSTCN-3 photocatalyst was added to 50 mL of deionized water and sonicated for 30 min to disperse it uniformly. Then, 0.75 g of sodium alginate (SA) was added and stirred vigorously for 6 h to mix thoroughly and form a pregel solution. The well-mixed pregel solution was transferred to a mold and then freeze-dried for 24 h to obtain a solid sponge. The solid sponge was immersed in 300 mL 3 wt% CaCl2 solution for 6 h to gel it. After thoroughly washing with deionized water and freeze-drying for 36 h, a sodium alginate gel sheet with CSTCN-3 attachment, i.e., SA@CDs / g-C3N4 composite, was obtained, whose physical form is sponge-like, so it is also called SA@CSTCN sponge. For comparison, in the present invention, the SA sponge was prepared under the same conditions without adding CSTCN photocatalyst.

[0014] Figure 5 shows the preparation flow chart of the SA@CSTCN sponge (a), the appearance of the SA sponge and the SA@CSTCN sponge (b), the SEM image of the SA@CSTCN sponge surface (c), and the SEM image of the SA@CSTCN sponge cross section (d). As shown in Fig. 5a, which is a schematic diagram of the preparation of the SA@CSTCN sponge, the ice crystals in the SA gel sublimated to form pores through the freeze-drying process. Then, the Ca 2+ The gel was cross-linked and solidified by adding photocatalyst, giving it a certain mechanical strength. In the absence of photocatalyst, the prepared SA sponge exhibited translucency, which indicated that light could well penetrate the SA gel matrix. Compared with the SA sponge, the SA@CSTCN sponge exhibited a yellow color, indicating that the catalyst was well dispersed (Figure 5b). As shown in Figures 5c and 5d of the SA@CSTCN sponge, the larger pores not only promoted the reflection of photons but also provided more reactive side. In addition, the abundant pores endowed the sponge with buoyancy and ensured a continuous supply of oxygen, facilitating the generation of ROS.

[0015] Application example 1 Removal of aflatoxin B1 in peanuts: 1 kg of peanuts were taken five times. 1 g of CSTCN (including CSTCN-1, CSTCN-3, CSTCN-5 and CSTCN-7) and 3 g of SA@CSTCN were added to the peanuts, and the mixture was stirred uniformly at a uniform speed of 230 rpm for 8 min, and 400 kg of pure water was added and mixed uniformly, and the mixture was exposed to light for 6 h and left to stand until solid-liquid separation occurred, and the supernatant was discarded and dried in the sun to remove aflatoxin B1 in the peanuts.

[0016] Take 5g of peanuts before and after detoxification according to the above method, add 10mL of cold methanol to elute, allow to stand, and then place 1mL of the suspension in a centrifuge tube, vortex shock for 2 minutes, and centrifuge at 4℃ and 10,000 rpm for 10 minutes. Analyze the aflatoxin concentration in the supernatant using high performance liquid chromatography (HPLC). If the toxin concentration is reduced by 85% or more, it meets the national standard requirements and is recorded as successful removal. The test results are shown in Table 1: Table 1 JPEG0007605541000002.jpg51147The above test results show that the CSTCN prepared by the present invention can effectively decompose and remove aflatoxin in peanuts. After combining CSTCN with SA to form SA@CSTCN, the material becomes sponge-like and is easy to recycle, so it has little impact on food quality.

[0017] Application example 2 Removal of aflatoxin B1 in peanut oil: 1 kg of peanut oil was taken five times. 1 g of CSTCN (including CSTCN-1, CSTCN-3, CSTCN-5 and CSTCN-7) and 3 g of SA@CSTCN were added to the peanut oil, and 10 kg of pure water was added. After shaking for 35 min, the mixture was stirred under light irradiation for 6 h, centrifuged at 10,000 rpm for 10 min, allowed to stand, and the aqueous layer was discarded, i.e., the water-insoluble aflatoxin B1 in the peanut oil was removed. 5 mL of peanut oil was taken before and after detoxification according to the above method, 5 mL of acetonitrile was added, and the oil was allowed to stand. 1 mL of the supernatant was placed in a centrifuge tube and centrifuged at 13,000 rpm and 4°C for 10 minutes. The aflatoxin concentration in the supernatant was analyzed using high performance liquid chromatography (HPLC). If the toxin concentration was reduced by 85% or more, it met the national standard requirements and was recorded as successful removal. The test results are shown in Table 2: Table 2 JPEG0007605541000003.jpg51147The above test results show that the CSTCN and SA@CSTCN sponges prepared according to the present invention are also effective in decomposing and removing aflatoxins in peanut oil.

[0018] The above content is only a preferred embodiment of the present invention, and does not limit the present invention in any way, and those skilled in the art can obtain equivalent embodiments by making equivalent changes such as modifications and variations to the technical content disclosed above. However, as long as it does not deviate from the content of the technical solution of the present invention, any simple modifications, equivalent changes and variations made to the above embodiments based on the technical essence of the present invention are all within the protection scope of the technical solution of the present invention.

Claims

1. CDs / g-C 3 N 4 The composite is added to water and ultrasonicated to disperse it uniformly, then sodium alginate is added, vigorously stirred and mixed thoroughly to form a pregel solution, the well-mixed pregel solution is transferred into a mold, and then freeze-dried to obtain a solid sponge, and the solid sponge is then cooled to 100°C. 2 The SA@CDs / g-C was gelled by immersion in the solution, then washed with deionized water and freeze-dried. 3 N 4 Obtaining a composite material, The CDs / g-C 3 N 4 The mass volume ratio of the composite to water is selected from 1:300 to 1:800 g / mL, and the CDs / g-C 3 N 4 The mass ratio of the composite to sodium alginate is selected from 1:4 to 1:10, and the CaCl 2 The concentration of the solution is selected from 1 to 8 wt %; The CDs / g-C 3 N 4 The steps of the method for preparing the composite are as follows: Melamine and trithiocyanuric acid are added to water and stirred uniformly, then the CDs solution is added and stirred uniformly, the mixed solution is filtered, washed and dried, transferred to a muffle furnace, and calcined at high temperature to obtain CDs / g-C. 3 N 4 Obtaining a compound, The molar ratio of the melamine to the trithiocyanuric acid is selected from 1:0.5 to 1:1.5, and the high-temperature firing conditions include heating to 550 to 650° C. at a rate of 2 to 6° C. / min and firing at this temperature for 3 to 6 hours, The steps of the preparation method of the CDs solution are as follows: Orange juice is placed in a polytetrafluoroethylene-lined reactor and heated at 180-210 °C for 8-12 h. After natural cooling, the reaction product is centrifuged and filtered to form a transparent brown-yellow carbon quantum dot solution, i.e., CDs solution, SA@CDs / g-C. 3 N 4 Methods for preparing composite materials.

2. The use of the SA@CDs / g-C 3 N 4 composite material prepared by the method of claim 1 in removing aflatoxins in food.

Citation Information

Patent Citations

  • Water decomposition photocatalyst, preparation method and applications thereof

    CN104857978A

  • Alginate-based composite carbon nitride catalytic aerogel material and preparation method and application thereof

    CN108686697A

  • Preparation method of carbon quantum dot modified graphite phase carbon nitride photocatalytic material

    CN109603879A

  • Novel antibacterial band-aid and preparation method and application thereof

    CN109875762A